Implementation of real-time probe-based confocal laser endomicroscopy (pCLE) for differentiation of colorectal polyps during routine colonoscopy - Belderbos, Tim D. G.; van Oijen, Martijn G. H.; Moons, Leon M. G.; Siersema, Peter D. (Endoscopy International Open, 2017)
Background and aims Probe-based confocal laser endomicroscopy (pCLE) is used to differentiate between neoplastic and non-neoplastic colorectal polyps during colonoscopy. We aimed to assess the accuracy of two endoscopists starting to use real-time pCLE for differentiation of colorectal polyps and to determine the negative predictive value (NPV) for neoplasia in polyps ≤ 5 mm.Methods Patients undergoing colonoscopy in a tertiary hospital were included in this prospective trial. After a training session, two colonoscopists assessed 50 polyps between August 2012 and April 2014. They sequentially used narrow-band imaging (NBI) and real-time pCLE to differentiate non-adenomatous, adenomatous, and carcinomatous polyps during colonoscopy. Histologic diagnosis by a gastrointestinal pathologist was the gold standard. Results were compared to post-hoc pCLE by a panel of gastroenterologists and pathologists.Results The accuracy of real-time pCLE was 76 %, compared to 73 % for NBI, and was not significantly different between the first 50 cases (74 %) and the last 50 cases (78 %, P = 0.64). The accuracy in polyps > 5 mm was 87 % versus 59 % in polyps ≤ 5 mm (P = 0.04) and increased from 45 % (13/29) in poor quality images to 86 % (44/51) in fair quality images and 95 % (19/20) in good quality images (P < 0.01). The post-hoc pCLE accuracy was 62 %. The NPV for polyps ≤ 5 mm was 58 % for real-time pCLE and 54 % for post-hoc pCLE.Conclusion Although a fair accuracy of real-time pCLE for differentiation of colorectal polyps can be achieved within 50 cases, low NPV and difficulty in obtaining high-quality pCLE images hamper implementation in routine clinical practice.